Review Terhadap Intervensi Pada Penderita Skizofrenia Dengan Gangguan Halusinasi Pendengar Di RS Y Jakarta - Marshela Belina; Arya Bima Prayoga; Wahyu Aulia Zalsini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This article is a review of Noviyana Prasati's research on Intervention in patients with Schizophrenia with Auditory Hallucinations who are treated in 2023. Schizophrenia is a psychiatric disorder when a person has difficulty thinking causing hallucinations. Schizophrenia can be cured but it takes a long time with the support of family, people around and education. Hallucinations are caused by a change in the perception of a person due to a stimulus that actually does not exist or something that actually does not happen. This study uses qualitative and quantitative methods and the author uses the literature review method. The result of this study is that the patient experiences auditory hallucinations caused by a small patient who has broken home and the patient fails to marry.